Overexpression of miR‐138‐5p suppresses MnCl2‐induced autophagy by targeting SIRT1 in SH‐SY5Y cells. Issue 4 (23rd January 2019) - Ma, Junxiang; Zhang, Yuanyuan; Ji, Hongyun; Chen, Li; Chen, Tian; Guo, Caixia; Zhang, Shixuan; Jia, Jiaxin; Niu, Piye
Abstract: The mechanism of manganism caused by manganese (Mn), an important environmental risk factor for Parkinson's disease, is still unclear. Recent evidence suggested that autophagy participated in neurodegenerative diseases, in which microRNA played a crucial role. However, roles of microRNA in the aberrant autophagy that occurs in neurodegenerative diseases remains controversial. In nervous system, miRNA‐138‐5p is highly expressed and plays a key role in regulating memory and axon regeneration. Importantly, we also found that miR‐138‐5p expression decreased significantly after SH‐SY5Y cells exposed to manganese chloride (MnCl2 ) in previous study. To explore the role of miR‐138‐5p in Mn‐induced autophagy, autophagy associated indicators were detected. And we found that MnCl2 could induce autophagic dysregulation and inhibit expression of miR‐138‐5p. While the levels of LC3‐II/LC3‐I, Beclin1, and p62, the number of autophagosome formation significantly decreased after miR‐138‐5p over‐expression, which demonstrated that miR‐138‐5p could clearly retard Mn‐induced autophagy. In additional, we found there were classical and evolutionarily conserved miR‐138‐5p binding sites in 3′‐UTR region of SIRT1, which was inhibited when overexpression of miR‐138‐5p. Therefore, it was speculated that elevated expression of SIRT1 may be resulted from inhibition of miR‐138‐5p after cells exposed to MnCl2 . Finally, we found that SIRT1 inhibitor EX‐527 suppressed Mn‐induced autophagy as well as miR‐138‐5p, while the suppression was reversed by SIRT1‐specific activator SRT1720. These results indicated that overexpression of miR‐138‐5p suppressed Mn‐induced autophagy by targeting SIRT1.